Autologous regulatory T cells in clinical intraportal allogenic pancreatic islet transplantation. (28th November 2021) - Bergström, Marcus; Yao, Ming; Müller, Malin; Korsgren, Olle; von Zur‐Mühlen, Bengt; Lundgren, Torbjörn
Summary: Allogeneic islet transplantation in type 1 diabetes requires lifelong immunosuppression to prevent graft rejection. This medication can cause adverse effects and increases the susceptibility for infections and malignancies. Adoptive therapies with regulatory T cells (Tregs) have shown promise in reducing the need for immunosuppression in human transplantation settings but have previously not been evaluated in islet transplantation. In this study, five patients with type 1 diabetes undergoing intraportal allogeneic islet transplantation were co‐infused with polyclonal autologous Tregs under a standard immunosuppressive regimen. Patients underwent leaukapheresis from which Tregs were purified by magnetic‐activated cell sorting (MACS) and cryopreserved until transplantation. Dose ranges of 0.14–1.27 × 10 6 T cells per kilo bodyweight were transplanted. No negative effects were seen related to the Treg infusion, regardless of cell dose. Only minor complications related to the immunosuppressive drugs were reported. This first‐in‐man study of autologous Treg infusion in allogenic pancreatic islet transplantation shows that the treatment is safe and feasible. Based on these results, future efficacy studies will be developed under the label of advanced therapeutic medical products (ATMP), using modified or expanded Tregs with the aim of minimizing the need for chronic immunosuppressive medication in islet transplantation. Abstract : First‐in‐man trial of adoptive cell therapy with autologous regulatory T cells in clinical intraportal allogenic pancreatic islet transplantation.